The scientification of China - Sun, Zhaohao (Cambridge Scholars Publishing, 2021)
This book provides a novel, strategic solution to where China will go in the coming decades, utilising the common interest shared by Chinese people and people from other countries to realize the common dream of all of mankind. It investigates the scientification of China, Chinese words, the Chinese language, and Chinese culture based on 10 scientific paradigms. Scientific Chinese words, scientific Chinese language and scientific Chinese culture form what is termed here as ‘the scientific Chinese trinity’, which will create a scientific China in the near future and facilitate the scientification of Chinese society and the development of the digital economy. The book will serve to convey to students, scholars, professionals, managers and practitioners the status of the evolution of Chinese culture and civilization.